PATIENT-REPORTED OUTCOMES IN RARE LYSOSOMAL STORAGE DISEASES: KEY INFORMANT INTERVIEWS AND A SYSTEMATIC REVIEW PROTOCOL. (28th December 2016) - Miller, Patricia A.; Mulla, Sohail M.; Adams-Webber, Thomasin; Sivji, Yasmin; Guyatt, Gordon H.; Johnston, Bradley C.
Abstract : Objectives: To investigate the use, challenges and opportunities associated with using patient-reported outcomes (PROs) in studies with patients with rare lysosomal storage diseases (LSDs), we conducted interviews with researchers and health technology assessment (HTA) experts, and developed the methods for a systematic review of the literature. The purpose of the review is to identify the psychometrically sound generic and disease-specific PROs used in studies with patients with five LSDs of interest: Fabry, Gaucher (Type I), Niemann-Pick (Type B) and Pompe diseases, and mucopolysaccharidosis (Types I and II). Methods: Researchers and HTA experts who responded to an email invitation participated in a telephone interview. We used qualitative content analysis to analyze the anonymized transcripts. We conducted a comprehensive literature search for studies that used PROs to investigate burden of disease or to assess the impact of interventions across the five LSDs of interest. Results: Interviews with seven researchers and six HTA experts representing eight countries revealed five themes. These were: (i) the importance of using psychometrically sound PROs in studies with rare diseases, (ii) the paucity of disease-specific PROs, (iii) the importance of having PRO data for economic analyses, (iv) practical and psychometric limitations of existing PROs, and (v) suggestions for new PROs. The systematic review has been completed. Conclusions: The interviews highlight current challenges and opportunities experienced by researchers and HTA experts involved in work with rare LSDs. The ongoing systematic review will highlight the experience, opportunities, and limitations of PROs in LSDs and provide suggestions for future research.